Barriers to family involvement in the care of patients with chronic mental illnesses: A qualitative study - Dehbozorgi, Raziye; Fereidooni-Moghadam, Malek; Shahriari, Mohsen; Moghimi-Sarani, Ebrahim (Frontiers in Psychiatry, 2022)
Introduction: Caregivers are patients’ family members or intimate friends who take care of individuals suffering from chronic mental illnesses without being paid. Evidence has supported the role of family-centered collaborative care in the treatment of patients with chronic mental illnesses. It has also been emphasized by national policies. However, carrying out this type of care is accompanied by challenges in Iran. Considering the importance of family participation in taking care of these patients as well as the necessity to determine its effective factors, the present study aimed to assess the barriers to family involvement in the care of patients with chronic mental illnesses. Method: A conventional content analysis was used to conduct this qualitative study. 34 health care providers, patients, and caregivers were interviewed unstructured in-depth face-to-face using purposive sampling. Until saturation of data, sampling and data analysis were conducted simultaneously. Graneheim and Lundman's method was used to record, transcribe, and analyze the interviews. Result: The results showed that there were many barriers to the collaboration of family in the care of patients with chronic mental illnesses. Accordingly, four main categories and twelve subcategories were extracted from the data as follows: "family-related barriers", "treatment-related factors", "disease nature threatening car", and "mental disease-associated stigma in the society". Conclusion: The findings presented the barriers to family centers' collaborative care in patients with chronic mental illnesses and the necessary components of family involvement in the care to be used by healthcare managers and policymakers. The reported barriers emphasize the need for the development of structured approaches whose implementation is easy for health care providers, does not require a lot of time and resources, and can improve patient and family outcomes.